Influence of nasal cavities on voice quality: Computer simulations and experiments - Vampola, Tomáš; Horáček, Jaromír; Radolf, Vojtěch; Švec, Jan G.; Laukkanen, Anne-Maria (The Journal of the Acoustical Society of America, 2020)
Nasal cavities are known to introduce antiresonances (dips) in the sound spectrum reducing the acoustic power of the voice. In this study, a three-dimensional (3D) finite element (FE) model of the vocal tract (VT) of one female subject was created for vowels [a:] and [i:] without and with a detailed model of nasal cavities based on CT (Computer Tomography) images. The 3D FE models were then used for analyzing the resonances, antiresonances and the acoustic pressure response spectra of the VT. The computed results were compared with the measurements of a VT model for the vowel [a:], obtained from the FE model by 3D printing. The nasality affects mainly the lowest formant frequency and decreases its peak level. The results confirm the main effect of nasalization, i.e., that sound pressure level decreases in the frequency region of the formants F1–F2 and emphasizes the frequency region of the formants F3–F5 around the singer's formant cluster. Additionally, many internal local resonances in the nasal and paranasal cavities were found in the 3D FE model. Their effect on the acoustic output was found to be minimal, but accelerometer measurements on the walls of the 3D-printed model suggested they could contribute to structure vibrations.